IMPLICATIONS OF CHROMOSOMAL ABNORMALITIES AND BENCE-JONES PROTEINS IN MULTIPLE MYELOMA - Balkanov, Svetlana Krstevska; Trajkova, Sanja; Pivkova Veljanovska, Aleksandra; Spasovski, Dejan; Ridova, Nevenka; Kalcev, Goce; Stavridis, Irina Panovska (Journal of Morphological Sciences; Vol 6 No 1 (2023): JMS, 2023)
Translocations are among the main genetic events responsible for multiple myeloma (MM). Also, in two thirds of MM cases, the presence of Bence Jones proteins is observed. The aim of this study was to demonstrate the role that chromosomal abnormalities and Bence-Jones proteins play as crucial biomarkers in MM patients. This retrospective study was carried out at the University Clinic for Hematology in Skopje, North Macedonia, between January 2009 and December 2019. MM patients were divided into different treatment groups: those younger than 65 years old, without comorbidities, and eligible for autologous peripheral blood stem cells (PBSCT) were included in the Cyclophosphamide-Thalidomide-Dexamethasone (CyThalDex) protocol group. The Melphalan Prednisone Thalidomide (MPT) protocol was used in patients over the age of 65 who were unsuitable for aggressive treatment options such as PBSCT due to comorbidities and renal failure. The third group's treatment did not include new immunomodulators like thalidomide. Molecular and chromosomal analyses were performed in 46 MM patients. The survival time of patients with MM concerning molecular and chromosome stratification showed that 20% of them were high-risk [hypodiploid (gain1q, loss1p) Del17p, Del13q, t(11;14) t(4;14) and multiple mutations] who survived 60 months, and the median survival time in these patients was 20.8 months. In patients with MM who had a standard risk, death outcomes were not registered during the observation period. Taking into account all MM patients included in our study, Bence Jones proteins in the urine were present in 35.8% of patients, while their presence was not observed in 64.2%. The percentage difference was statistically significant. The use of these critical biomarkers in the clinical background of this disease in the future can only be achieved through careful evaluation and validation in clinical trials. Keywords : multiple myeloma; chromosomal aberrations; Bence-Jones protein; molecular investigation. https://doi.org/10.55302/JMS2361143kb